Seleção de clones de cajueiro-anão por meio da qualidade de pedúnculos - Evangelista, Jaiane da Silva Barbosa (2017)
In order to select dwarf cashew clones (Anacardium occidentale L. var. Nanum) from the qualitative attributes of the peduncle, for commercialization of natural ones or for the processing industry, 25 clones selected from a competition experiment in rainfed, in the experimental field of Pacajus-CE of the Embrapa Tropical Agroindustry. Clones CCP 76 and BRS 226 were used as controls. Cashews were harvested from August to December 2015 and evaluated for the following characteristics: mass (total, peduncle and chestnut), size (apical and basal diameters and length), firmness, pH, acidity, soluble solids, SS/AT, soluble sugars, total extractable polyphenols and vitamin C. Among the evaluated materials, the MG CAP-113 stood out because it is superior to the controls in almost all the physical characteristics. In general, most of the clones presented characteristics similar to those of the controls. The CAP Pro-112/8 and CAP Pro-145/7 clones were lower in the SS/AT ratio and the others matched at least one of the two controls. The CAP Pro-112/8 clone stood out to have almost 62% more vitamin C than the average of the controls. The PET values ranged from 107.56 to 538.27 mg EAG.100 g-1 of pulp among the clones. CAP Pro-121/1, CAP Pro-145/7, CAP Pro-150/3, and CAP H-111/2 clones can be indicated for processing only and all the others have dual aptitude, and can be selected for both, the in natura consumption and for the processing.